Radiolabeled Peptide as Diagnostic, Therapeutic, and Theranostic agents for Prostate Cancer: Systematic Literature Review - Syabrina Salsabilah Gili; Muzakkir Baitz; Nurmaya Effendi (Universitas Muslim Indonesia, 2022)
Prostate cancer (PCa) is the most common sex-related malignancy and the second most common cause of mortality after lung cancer for men. Around 61.8% of Indonesian people undergo cancer treatment with surgery. This study aimed to figure out the use of radiolabeled peptides for diagnosis, therapy, and theranostics of prostate cancer. This study performed a literature review by searching the web databases such as PubMed, MDPI, Elsevier (Science Direct), and ACS Publications. The result showed that peptide compounds such RM2, VCN (Vicrostatin), DB15, and BBN7-14 were utilized as radionuclide-carriers for diagnostic imaging, meanwhile, peptides such as NeoBOMB1, PSMA-617, and [RGD-Glu-[DO3A]-6-Ahx-RM2] containing alpha or beta-emitted radionuclide were used as therapeutic and theranostic agents. They were tagged using 68Ga, 161Tb, 177Lu, 64Cu, 124I, 99mTc, 90Y, and 86Y radionuclides. Great efforts have been conducted in developing peptide-based radiopharmaceuticals for diagnosis and therapy of prostate cancer. Research groups focusing in nuclear medicine will continue to develop radiopharmaceuticals in the future, especially radiopeptide compounds for the diagnosis and therapy of prostate cancer.